MULTIMODAL TREATMENT STRATEGIES IN ENDOMETRIOSIS: A CONTEMPORARY SYSTEMATIC REVIEW OF MEDICAL AND SURGICAL MANAGEMENT - Aleksandra Wójciak,; Magdalena Zięba,; Magdalena Morytko,; Maja Elertowicz,; Mikołaj Moskwa,; Patrycja Herod,; Szymon Rudawski,; Kateryna Shtohryn,; Hubert Gugulski, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Endometriosis is a chronic, estrogen-dependent disorder characterized by ectopic endometrial-like tissue, chronic pelvic pain and impaired fertility. Optimal management requires balancing symptom control, recurrence prevention and preservation of reproductive potential. This review synthesizes evidence on contemporary pharmacological, postoperative and non-pharmacological strategies to inform multidisciplinary care.Methodology: A literature review of PubMed, Scopus, and Google Scholar was performed, focusing on recent systematic reviews and meta-analyses evaluating surgical, pharmacological, non-pharmacological, and assisted reproductive strategies for endometriosis.Results: Progestogens (notably dienogest) and continuous/extended COCs reduce dysmenorrhea and chronic pelvic pain and serve as viable long-term maintenance. Oral GnRH antagonists provide rapid, dose-dependent analgesia with add-back strategies mitigating hypoestrogenic harms. Surgical excision may yield superior symptom relief and lower recurrence in selected phenotypes but risks ovarian reserve loss, tissue-paring techniques can attenuate this effect. Postoperative hormonal suppression (≥6–12 months) reduces recurrence. Integrated non-pharmacological modalities improve pain coping, adherence and HRQoL. Endometriomas and deep disease negatively affect ovarian response and implantation, supporting individualized pre-ART planningConclusion: Effective endometriosis management requires an individualized, multimodal approach integrating surgery, medical therapy, supportive care, and fertility planning. Holistic strategies enhance quality of life, reduce pain, and optimize reproductive outcomes. Interdisciplinary coordination is key to tailoring therapy according to patient phenotype, reproductive goals, and disease severity.